Haemophilia and knee function - Seuser, A.; Schumpe, G.; Schuhmacher, M.; Lehmacher, K.; Oldenburg, J.; Berdel, P. (Hämostaseologie, 2009)
With early prophylactic treatment our haemophilic children grow up in good health. Nevertheless, we cannot prevent every bleeding. Those bleedings may be just subclinical but they could lead to overloading of the knee and more and more of the ankle joint in the long term. Motion analysis can help to understand this process and prevent it. A comparison of the gait function of haemophilic and healthy children of the age 3–18 years showed distinct functional differences especially in the youngest age group (3–6 years). Apparently, the coordination skill gait rhythm was significantly worse in the heamophilic group. All measured functional deficits can be treated with physiotherapy. Possible reasons for these early functional differences are overprotection and/or early subclinical bleedings.
Keywords: Subclinical bleeds; prophylactic treatment; threedimensional motion analysis